A novel potential source of β-carotene: Eustigmatos cf. polyphem (Eustigmatophyceae) and pilot β-carotene production in bubble column and flat panel photobioreactors - Li, Zhen; Ma, Xiaoqin; Li, Aifen; Zhang, Chengwu (Bioresource technology, 2012)
► Carotenoids profile of Eustigmatos cf. polyphem was first analyzed by HPLC. ► The microalga was first reported to accumulate large amount of β-carotene and biomass. ► Effects of light intensity and N on β-carotene and biomass accumulation were studied. ► Production of β-carotene in bubble column and large flat panel bioreactors was assessed. Carotenoids profile of the unicellular Eustigmatos cf. polyphem (Eustigmatophyceae) and β-carotene production of the microalga in bubble column and large flat panel bioreactors were studied. The microalga which contained β-carotene, violaxanthin and vaucheriaxanthin as the major carotenoids accumulated large amount of β-carotene. The β-carotene production of this microalga in the bubble column bioreactor was considerable, with the maximum intracellular β-carotene content reaching 60.76mgg−1, biomass reaching 9.2gL−1, and β-carotene yield up to 470.2mgL−1. The β-carotene productions in two large flat panel bioreactors were relatively lower, whereas over 100mg β-carotene L−1 was achieved. Besides, high light intensity helped to accumulate intracellular β-carotene and biomass. Deficient nitrate supply inhibited biomass growth, though it helped to accumulate β-carotene. Our results first proved that E. cf. polyphem was a potential source and producer of β-carotene, making it an interesting subject for further β-carotene study or commercial exploration.